Adaptive output-feedback control with prescribed performance for trajectory tracking of underactuated surface vessels. (December 2019) - Jia, Zehua; Hu, Zhihuan; Zhang, Weidong
Abstract: In this paper, we address the problem of trajectory tracking control of underactuated surface vessels in a quantitative method with only position and attitude available. Combined with high-gain observer, parameter compression algorithm and performance function, an adaptive control scheme with prescribed performance is proposed. The high-gain observer is constructed to estimate the velocities, and the parameter compression algorithm is adopted to address persistent perturbations and model uncertainties in a more concise way. By prescribed performance function, the controller can be designed with prescribed performance. The results about system stability is given and proved by using the Lyapunov direct method. The signals concerning with all the errors converge to a bounded set. Compared with the existing methods, the developed scheme can reduce the number of tuning parameters, and guarantee the tracking errors bounded within the prescribed performance constraints in the transformed coordinate, which means the steady errors, convergence rates and maximum overshoots can be guaranteed by the performance function. Comparison and numerical simulations are given to demonstrate the effectiveness of the proposed scheme. Highlights: An adaptive control scheme is proposed with only position and yaw angle available. Parameter compression algorithm is adopted to reduce the number of tuning parameters. The proposed scheme can guarantee the tracking errors with prescribed performance.